Smith-Peterson osteotomy and lordotic posterior column compressive screw fixation proceed by postural pillow reduction improved realignment for unstable lumbar burst fracture - Farid Yudoyono; Hasan Baraqbah; Deasy Herminawaty (Indoscholar, 2020)
Lumbar burst fractures (LBF) is a common trauma case of the spine, recently still a difficult problem to solve. Experts have published the approaches and techniques, but there is still a high incidence of morbidity and mortality, unsatisfactory clinical and radiological results especially in developing countries. The minimal tissue destruction approach with rigid screw-rod construction allowed to lowering surgical costs and earlier patient recovery with successfully clinical and radiological results in the short term follow up.